Characterization of High-power DFB-MOPA Diode Lasers Emitting at 1064 nm - Nguyen, Thanh-Phuong (Communications in Physics, 2019)
Detail characterization of the such laser diode is important for the applications. Electro-Optical and spectral characteristics of the high power 1064 nm DFB-MOPA lasers are investigated at room temperature as function of injection current. Beam quality is characterized by waist diameter and far-field divergence angle versus average optical output power. Beam propagation ratio M2 is defined at difference intensity levels from lateral beam profile giving more detail laser behaviors at high power.